Download presentation

Presentation is loading. Please wait.

Published byAvis Robbins Modified over 4 years ago

1
Solving a system of equations by adding or subtracting

2
2x + 3y = 11 -2x + 5y = 13 When using the adding or subtracting method, one of the variable combinations can completely eliminate themselves if you were to combine the 2 equations together In this example, the X’s can Eliminate themselves 8y = 24 88 y = 3 What we know now is that the answer will be (?, 3) To find the value of x you Use either equation from The question and substitute In to find your answer 2x + 3(3) = 11 2x + 9 = 11 -9 2x = 2 22 x = 1 The Answer Is (1, 3)

3
4x + 3y = 2 5x + 3y = -2 When using the adding or subtracting method, one of the variable combinations can completely eliminate themselves if you were to combine the 2 equations together In this example, the Y’s can eliminate themselves If we do 1 thing first -1x = 4 x = -4 What we know now is that the answer will be (-4, ?) To find the value of y you Use either equation from The question and substitute In to find your answer 4(-4) + 3y = 2 -16 + 3y = 2 +16 3y = 18 33 y = 6 The Answer Is (-4, 6) -5x – 3y = 2

4
8x – 4y = -4 4y = 3x + 14 In this example, we need for both equations to be in the same form. I am going to put the bottom equation into standard form to solve. 5x = 10 55 x = 2 What we know now is that the answer will be (2, ?) To find the value of y you Use either equation from The question and substitute In to find your answer 8(2) - 4y = -4 16 - 4y = -4 -16 -4y = -20 -4 y = 5 The Answer Is (2, 5) -3x + 4y = 14

5
Pg. 447 4 – 20 even

Similar presentations

© 2019 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google